2015
DOI: 10.1002/chem.201502629
|View full text |Cite
|
Sign up to set email alerts
|

From Saturated BN Compounds to Isoelectronic BN/CC Counterparts: An Insight from Computational Perspective

Abstract: In the present study, the inorganic analogues of alkanes as well as their isoelectronic BN/CC counterparts that bridge the gap between organic and inorganic chemistry are comparatively studied on the grounds of static DFT and Car-Parrinello molecular dynamics simulations. The BN/CC butanes CH3 CH2 BH2 NH3 , BH3 CH2 NH2 CH3 , and NH3 CH2 BH2 CH3 were considered and compared with their isoelectronic counterparts NH3 BH2 NH2 BH3 and CH3 CH2 CH2 CH3 . In addition, systematical replacement of the NH2 BH2 fragment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 102 publications
3
18
0
Order By: Relevance
“…Further, quite unintuitive at first glance anion ··· π interactions have been found to be crucial for not only for crystal engineering, but also for reactions in condensed phases . Later, it became clear that even polar hydrogen‐hydrogen bonds X–H δ + ··· – δ H–Y (X ≠ Y) can constitute a real gluing force in supramolecular chemistry …”
Section: Introductionmentioning
confidence: 99%
“…Further, quite unintuitive at first glance anion ··· π interactions have been found to be crucial for not only for crystal engineering, but also for reactions in condensed phases . Later, it became clear that even polar hydrogen‐hydrogen bonds X–H δ + ··· – δ H–Y (X ≠ Y) can constitute a real gluing force in supramolecular chemistry …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the former feature of ammonia borane crystal originates predominantly from the existence of polar dihydrogen bonds N-H δ`¨¨¨´δ H-B between monomers [11][12][13][14][15][16]. Furthermore, it has been proven that the presence of N-H δ`¨¨¨´δ H-B as well as other non-covalent interactions not only determines the stability, but it can also facilitate various steps of dehydrogenation [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In 2, the cation is a doubly charged centrosymmetric dinuclear structure with two Zn II [57][58][59][60][61] study, that the seven-membered rings in 1-3 constitute a quasi-aromatic Möbius-type motif, though the absolute magnitude of such p-delocalization is notably weaker than in the corresponding cadmium-based analogs. 24,27 Bulkiness of the ligands (L) are found not only to amplify London dispersion stabilization, 24,27,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] but also inuence the magnitude of quasi-p-delocalization (of Möbius-type) through modi-cation of the polarity of Zn-L bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the DE disp term is consistent with recent ndings, which rediscover the importance of London dispersion forces in small and sizeable species. 24,27,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] In 3 the [Zn(NCS) 4 ] 2À anion sticks very strongly (DE int ¼ À193.21 kcal mol À1 ) to two neighboring stacked [Zn(NCS)L II ] + units primarily through electrostatic forces (75.3% of the overall stabilization) (Fig. 5).…”
mentioning
confidence: 99%
See 1 more Smart Citation